Purifying Effect Evaluation of Pavement Surfacing Materials Modified by Novel Modifying Agent - Sun, Xiaolong; Liu, Zhisheng; Qin, Xiao; Zeng, Dongfang; Yin, Yingmei (Frontiers in Materials, 2020)
Functional pavement material with exhaust-purifying performance has been focused gradually in recent years. For improving the purifying effect of functional micro surfacing, two types of raw ore powders with exhaust-purifying potentials were selected as novel functional modifiers. Firstly, the road performance of purifying micro surfacing was evaluated according to the ASTM and ISSA standards. Then, the dispersion state of modifying agent in emulsified asphalt evaporation residue was analyzed and discussed through using SEM and FTIR. Finally, the purifying effect of micro surfacing on exhaust was examined in laboratory to investigate the impact of various experimental conditions on purifying performance. Meanwhile, the purifying performance was also monitored in field test. The results showed that road performance of purifying micro surfacing could fulfill the requirements of relevant technical standards. Pyrite had better dispersion property than specularite and titanium dioxide inside asphalt. The purifying micro surfacing could achieve better purifying effect on NOx and COx than traditional micro surfacing with TiO2. These environmental-friendly pavement materials would provide new solutions for the reduction in polluting emissions of automobile exhausts.